2020
DOI: 10.1111/jcmm.16046
|View full text |Cite
|
Sign up to set email alerts
|

LINC01128 regulates the development of osteosarcoma by sponging miR‐299‐3p to mediate MMP2 expression and activating Wnt/β‐catenin signalling pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Osteosarcoma is the most common primary aggressive malignancies of the skeleton, and it occurs mainly in children and adolescents, in which distant metastasis still leads to a poor prognosis (Chow et al, 2020;Rojas et al, 2021). With a combination of neoadjuvant chemotherapy, surgery, chemotherapy, and biological therapy in the last few years, the 5-year survival rate for osteosarcoma patients has improved significantly, from 20% to 65-70% (Yao and Chen, 2020;Gazouli et al, 2021). However, due to the limited efficacy of current treatment strategies, nearly 30% of osteosarcoma patients are prone to metastasis or recurrence, with poor prognosis and low 5-year survival rates (Fan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma is the most common primary aggressive malignancies of the skeleton, and it occurs mainly in children and adolescents, in which distant metastasis still leads to a poor prognosis (Chow et al, 2020;Rojas et al, 2021). With a combination of neoadjuvant chemotherapy, surgery, chemotherapy, and biological therapy in the last few years, the 5-year survival rate for osteosarcoma patients has improved significantly, from 20% to 65-70% (Yao and Chen, 2020;Gazouli et al, 2021). However, due to the limited efficacy of current treatment strategies, nearly 30% of osteosarcoma patients are prone to metastasis or recurrence, with poor prognosis and low 5-year survival rates (Fan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the indispensable roles of these two lncRNAs in tumor development and progression in different tumor types. 60 , 61 , 62 On the basis of the above-mentioned binding between miR-6077 and these two lncRNAs, as well as the functional experiments measuring cytotoxicity, cell-cycle percentage, and ferroptosis, we determined that GMDS-AS1 and LINC01128 sensitize LUAD cells to CDDP/PEM by negatively regulating the miR-6077-CDKN1A/KEAP1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of these genes is regulated by lncRNAs. For example, LINC01128 plays a regulatory role in cell invasion, migration, and proliferation through the LINC01128/miR-299-3p/MMP2 axis [ 44 ]. Based on the above analysis, we speculated that the lncRNAs Tcons_00021399 and Tcons_0009334 may play an essential role in regulating molecular mechanisms related to ECM recombination or spermatogenesis in goat testis.…”
Section: Discussionmentioning
confidence: 99%